Routes to achieving sustainable intensification in simulated dairy farms: The importance of production efficiency and complimentary land uses. Issue 5 (19th February 2019) - White, Patrick J. C.; Lee, Mark A.; Roberts, Dave J.; Cole, Lorna J.
Abstract: Sustainable intensification (SI) is a global challenge, aiming to increase food production whilst conserving biodiversity and ecosystem services. This is contrary to the observed trend of agricultural intensification degrading environmental quality. We developed a framework integrating animal nutrition, crop yields and biodiversity modelling to explore SI potential in multiple model dairy farming systems through varying crop composition to provide cattle feed rations. We then identified key drivers of biodiversity gain that may be applicable at a wider scale. We developed multiple feed rations to meet the nutritional demands of a high‐yielding, housed dairy herd. The land area required varied due to productivity and nutritional differences between crops, generating spare land. We used published biodiversity models to compare alpha‐ and beta‐diversity of spiders and plants across 36 scenarios that used the spare land in different ways, for either biodiversity maximisation or additional production. Alpha and beta‐diversity for both taxa was the greatest in scenarios that maximised spare land and utilised this for species‐rich extensive grassland. However, commensurate biodiversity gains for plant alpha‐diversity, and spider and plant beta‐diversity (respectively 100%, 76% and 86% gain relative to that optimal scenario) were achievable when spare land was used for additional crop production. Maximising compositional heterogeneity and adding complementary productive land uses to spared land were key to increasing production and beta diversity, while adding species‐rich productive land uses drove increasing production and alpha diversity. Synthesis and applications . This study indicates the potential for the sustainable intensification of dairy farming systems through the manipulation of feed rations to increase land efficiency and spare land, which could then be used to enhance production and biodiversity. The optimum land composition depends on target goal(s) (e.g. maximising production and/or biodiversity). The greatest 'win‐wins' can be achieved by making land cover more diverse and selecting crops that complement each other in the species they support; highlighting the important role of heterogeneity in the crop matrix. Our study provides a framework that integrates agricultural production efficiency and biodiversity modelling to explore potential routes to achieve sustainable intensification goals. Abstract : This study indicates the potential for the sustainable intensification of dairy farming systems through the manipulation of feed rations to increase land efficiency and spare land, which could then be used to enhance production and biodiversity. The optimum land composition depends on target goal(s) (e.g. maximising production and/or biodiversity). The greatest 'win‐wins' can be achieved by making land cover more diverse and selecting crops that complement each other in the species they support; highlighting the important role of heterogeneity in the crop matrix. Our study provides a framework that integrates agricultural production efficiency and biodiversity modelling to explore potential routes to achieve sustainable intensification goals.